2012
DOI: 10.1111/j.1468-1331.2012.03777.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cerebrospinal fluid neurofilament light levels in patients with amyotrophic lateral sclerosis: a possible marker of disease severity and progression

Abstract: High CSF NFL levels were found in patients with ALS, reflecting the burden of neurodegeneration. The significant relation between CSF NFL levels and disease progression suggests that NFL may be a useful marker of disease activity and progression in ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 36 publications
5
99
0
Order By: Relevance
“…Similar to pNFH, increased levels of NFL were correlated with rate of progression, as monitored by the rate of decline in ALSFRS-R scores, as well as upper MN involvement [36,39]. A rapid time to generation (time of symptom spreading from bulbar or spinal localization to both) has also been noted with increased CSF NFL [37].…”
Section: Neurofilament Proteinsmentioning
confidence: 64%
See 1 more Smart Citation
“…Similar to pNFH, increased levels of NFL were correlated with rate of progression, as monitored by the rate of decline in ALSFRS-R scores, as well as upper MN involvement [36,39]. A rapid time to generation (time of symptom spreading from bulbar or spinal localization to both) has also been noted with increased CSF NFL [37].…”
Section: Neurofilament Proteinsmentioning
confidence: 64%
“…Many studies have also examined levels of NFL in ALS and control groups [35][36][37][38]. Similar to pNFH, increased levels of NFL were correlated with rate of progression, as monitored by the rate of decline in ALSFRS-R scores, as well as upper MN involvement [36,39].…”
Section: Neurofilament Proteinsmentioning
confidence: 98%
“…Phosphorylated neurofilament heavy chain appears elevated at stable levels throughout the disease [19][20][21][22][23][24][25][26]. Neurofilament light chain in cerebrospinal fluid (CSF) appears to increase as ALS progresses [19,[27][28][29][30][31]. Urate, which is lower in people with ALS than in controls, could serve a predictive or prognostic role [32][33][34][35][36].…”
Section: Toward Novel Outcome Measures and Biomarkers In Als Trialsmentioning
confidence: 99%
“…To aid diagnostics, patient stratification and studies seeking to find further treatments for these diseases, there is a need to establish a way to reliably and objectively assess disease severity and the amount of ongoing neurodegeneration. Previous studies have suggested that cerebrospinal fluid (CSF) neurofilament light (NFL) may serve this purpose (Tortelli et al, 2012, Menke et al, 2015. NFL is part of a family of proteins with all members acting as important parts of the scaffolding of the neuronal and axonal cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%